2020
DOI: 10.3390/ijerph17124224
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Quality and Psychological Status in a Group of Italian Prisoners

Abstract: Prison could be considered a prolonged stressful situation that can trigger not only a dysregulation of sleep patterns but can also bring out psychiatric illness, such as anxiety and depression symptoms. Our study is aimed at exploring sleep quality and sleep habits in an Italian prison ward with three different security levels, and to attempt to clarify how anxiety state and the total time spent in prison can moderate insomnia complaints. There were 129 participants divided into three groups who enrolled in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…The most common mental disorders amongst Italian prisoners are psychosis, dissociation, affective disorders, anxiety disorders, personality disorders, substance abuse disorders, and comorbidities [ 11 , 12 , 13 , 14 ]. Suicide is much more frequent in prison settings than in the general population [ 15 ], and, in Italian prisons, one in every 10 prisoners engages in self-injurious behaviour [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most common mental disorders amongst Italian prisoners are psychosis, dissociation, affective disorders, anxiety disorders, personality disorders, substance abuse disorders, and comorbidities [ 11 , 12 , 13 , 14 ]. Suicide is much more frequent in prison settings than in the general population [ 15 ], and, in Italian prisons, one in every 10 prisoners engages in self-injurious behaviour [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of sleep-associated factors, studies reviewed found a correlation between insomnia and several mental health disorders and other factors. These included: PTSD (Acar et al , 2019; Geng et al , 2020); depression and gambling addiction (Geng et al , 2020); anxiety and mood alteration (D’Aurizio et al , 2020); a history of sedative use and use of multiple substances (Chinichian and Alemohammad, 2020); rape conviction, criminal assault conviction, use of marijuana and hashish, current use of coffee and poor sleep hygiene (Getachew et al , 2020); and lower pro-social attributes and greater levels of aggression (Barker et al , 2016). These associations add to the pre-2015 findings of Dewa et al ’s (2015) review that insomnia is associated with psychiatric disorders (including specific diagnosis of personality disorder, depression and anxiety), substance misuse (mixed results: a significant association with opiate and cocaine use but not cannabis) and pain.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining three papers were focussed on associated factors. These included: PTSD (Acar et al , 2019); anxiety and mood alteration (D’Aurizio et al , 2020); lower pro-social attributes and greater levels of aggression (Barker et al , 2016). Some of the papers found in the above “prevalence” group also reported associated factors, which are considered in the discussion section.…”
Section: Secondary Analysismentioning
confidence: 99%
“…A general psychiatric evaluation was performed for the patient's sleep disturbance and mood by a clinical psychologist at the Institute of Clinical Psychology using the Beck Depression Inventory (BDI-2) to evaluate depression, the State-Trait Anxiety Inventory (STAI) to evaluate anxiety and the Beck Hopelessness Scores to evaluate hopelessness. 10,11 The clinical severity of chronic spontaneous urticaria was evaluated using the Urticaria Severity Score by Jariwala et al, with a total score of 92 points. 12 For the evaluation of abdominal pain, a gastroenterologist examined the patient.…”
Section: Case Presentationmentioning
confidence: 99%